Photosynthetic Acclimation to Fluctuating Irradiance in Plants - Morales, Alejandro; Kaiser, Elias (Frontiers in Plant Science, 2020)
Unlike the short-term responses of photosynthesis to fluctuating irradiance, the long-term response (i.e. acclimation) at the chloroplast, leaf and plant level have received less attention so far. The ability of plants to acclimate to irradiance fluctuations and the speed at which this acclimation occurs are potential limitations to plant growth under field conditions, and therefore this process deserves closer study. In the first section of this review, we look at the sources of natural irradiance fluctuations, their effects on short-term photosynthesis and the interaction of these effects with circadian rhythms. This is followed by an overview of the mechanisms that are involved in acclimation to fluctuating (or changes of) irradiance. We highlight the chain of events leading to acclimation: retrograde signaling, systemic acquired acclimation, gene transcription and changes in protein abundance. We also review how fluctuating irradiance is applied in experiments and highlight the fact that they are significantly slower than natural fluctuations in the field, although the technology to achieve realistic fluctuations exists. Finally, we review published data on the effect of growing plants under fluctuating irradiance on different plant traits, across studies, spatial scales and species. We show that, when plants are grown under fluctuating irradiance, the chlorophyll a/b ratio and plant biomass decrease, specific leaf area increases, and photosynthetic capacity as well as root/shoot ratio are, on average, unaffected.